ISLAMIC PERSPECTIVES ON SCIENCE AND ETHICS: A CONTRAST WITH SECULAR AND CHRISTIAN VIEWS - Agustono, Ihwan; Inayah, Firda (Universitas Al-Amien Prenduan, 2024)
This paper discusses the interrelation of worldviews, science, language, and religion by comparing the secular, Christian, and Islamic perspectives. The worldview within which humanity exists plays a major role in shaping human perception. The Islamic worldview incorporates ethics into the body of scientific knowledge and entrusts humans with obligations toward the Earth, labeling them as Khalifah. Proceeding with this approach, the research undertaking a literature review and thematic analysis pursues the study of primary and secondary sources made up of the Holy Qur’an, Hadith, and relevant academic literature. By examining this Qur’anic and Hadith-based model of ethics, what is revealed is how Islam inspires an attitude toward knowledge acquisition in a manner that is moral in content, where scientific progress is weighed against social and ecological obligations. The findings stress the role of worldview in the formation of scientific thought, using language, and religious perceptions while focusing on how the Islamic worldview uniquely integrates ethics into science and knowledge. This work adds to a holistic understanding of the ways in which worldview serves as a guide for action in developing insights into the interconnection of faith, science, and ethics within the Islamic tradition.